2009
DOI: 10.1111/j.1755-3768.2008.01217.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between ocular pulse amplitude and systemic blood pressure measurements

Abstract: ABSTRACT.Purpose: This study aimed to determine whether ocular pulse amplitude (OPA) measured with dynamic contour tonometry (DCT) is related to systemic blood pressure (BP) parameters. Methods: Blood pressure was measured continuously and simultaneously with OPA in one randomly selected eye in 29 healthy subjects. Systemic parameters of interest were: systolic and diastolic BPs and their difference (BP amplitude), and left ventricle ejection time (LVET; defined as the time between the diastolic trough and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
1
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 36 publications
5
41
1
7
Order By: Relevance
“…This is illustrated by the observation that a defined blood volume change in the choroid results in a smaller relative change in pressure in myopic eyes than in shorter emmetropic eyes [5,56]. In addition, the reduced scleral rigidity in myopic eyes results in less resistance to enlargement of the pulsatile volume [59].…”
Section: Opa and Glaucomamentioning
confidence: 99%
See 1 more Smart Citation
“…This is illustrated by the observation that a defined blood volume change in the choroid results in a smaller relative change in pressure in myopic eyes than in shorter emmetropic eyes [5,56]. In addition, the reduced scleral rigidity in myopic eyes results in less resistance to enlargement of the pulsatile volume [59].…”
Section: Opa and Glaucomamentioning
confidence: 99%
“…By recording the pulsatile component of the ocular blood flow over a period of time, the OPA may provide an indirect measurement of the uveal blood volume changes during the cardiac cycle, as the choroid represents most of the ocular blood volume and receives 80-90% of the local flow [3]. Accordingly, OPA has been proposed as an index of ocular hemodynamics [4,5]. Furthermore, it has been suggested as a surrogate outcome for extraocular hemodynamics, the rationale being that anything that interferes with ocular perfusion will likely affect OPA measurements.…”
Section: Introductionmentioning
confidence: 99%
“…19 The relationship between ocular pulse amplitude (OPA) and hemodynamic changes was also investigated in some studies. 20,21 OPA can be measured with dynamic contour tonometer, which is a nonapplation tonometer. It measures IOP levels and OPA without influence of anterior segment structures by a contour matched pressure sensing tip.…”
Section: Introductionmentioning
confidence: 99%
“…In an initial study, blood pressure was found to be correlated with OPA (Pourjavan, 2007). Subsequent studies could not confirm an impact of blood pressure on OPA (Grieshaber MC., 2009) and found no correlation with the blood pressure amplitude itself (Choi J., 2010). However, there have been case reports of OPA being increased in patients with aortic insufficiency (McKee HD., 2004) and decreased in patients with carotid stenosis (Perkins, 1985).…”
Section: Altered Blood Flow As a Risk Factor For Glaucoma (Progression)mentioning
confidence: 99%
“…Further reports about increases in OPA after correcting upstream arterial stenosis (Kaufmann C., 2002) give support to the intuitive notion that blood pressure might yet be important. Of note, the studies that have ruled out a relationship between blood pressure and OPA were either performed in young healthy volunteers (Grieshaber MC., 2009) or in glaucoma patients with normal arterial blood pressure (Choi J., 2010).…”
Section: Altered Blood Flow As a Risk Factor For Glaucoma (Progression)mentioning
confidence: 99%